Dual-wavelength pulsed dye laser inhibits proliferation and promotes apoptosis of hemangioma vascular endothelial cells - Qi DI; Sanlin LI; Gaolei ZHANG; Chenghao CHEN; Jiajie CAO; Yi XIONG; Jing ZHANG; Hao WANG; Jing LIU; Gang SHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To investigate the effects of dual-wavelength pulsed dye laser on the proliferation and apoptosis of hemangioma vascular endothelial cells (HemECs). Methods The isolated HemECs were randomly divided into four groups: pulsed dye laser group (PDL, 595 nm wavelength), Nd∶YAG laser (1 064 nm wavelength) group, dual-wavelength group (595 nm PDL+1 064 nm Nd∶YAG) and control group (no laser treatment). After 1, 3, and 7 d of treatment, the proliferation and apoptosis rate of HemECs were detected using CCK-8 and flow cytometry,respectively. The expression levels of angiogenesis related proteins, VEGF and bFGF, were detected with Western blotting. Results Compared with the control group, laser treatment made HemECs longer and sparser. After one day of treatment, the dual-wavelength laser significantly inhibited HemEC proliferation (P=0.015). However, neither PDL nor Nd∶YAG significantly changed proliferation rate of HemECs (P>0.05 vs. controls). After 3 and 7 days of treatment, the proliferation activity, expression levels of VEGF and bFGF proteins of HemECs were markedly decreased in the all laser-treated groups (P<0.001 vs. controls), while the rates of proliferation inhibition and apoptosis were significantly increased (P<0.001 vs. controls), with a more prominent effect in the dual-wavelength laser-treated group (P<0.05 vs. PDL and Nd∶YAG groups). Conclusions Dual-wavelength pulsed dye laser can significantly inhibit the proliferation and promote apoptosis of HemECs, in addition to reduction in expression levels of angiogenesis factors. The effects of dual-wavelength pulsed dye laser are superior to that of either 595 nm PDL or 1 064 nm Nd∶YAG single wavelength laser.